Breastfeeding peer support affecting early complementary feeding in babies ages 0-4 monts - Aris Prastyoningsih; Rini Sumiyati Astutiningsih (International Journal of Health Science and Technology, 2019)
One step in the success of breastfeeding is to refer the mother to the Breastfeeding peer support after the mother returns from the health service. the existence of support group for breastfeeding mothers is an important factor that can support the success of mothers for breastfeeding. (Bevan and Brown, 2014). The existence of peer support for breastfeeding mothers can also increase initiation breastfeeding, the duration of exclusive breastfeeding and the satisfaction of mothers with breastfeeding (Vari et al., 2000; Lawrence, 2000). The aim of research is to determine effect of breastfeeding peer support on early complementary feeding in infant. The type of research used is case control research. This research is carried out in primary health care of Ampel 1, Boyolali District, Indonesia. The sampling method using quota sampling technique with a total sample of 30 respondents. The analysis used is the Chi Square formula. The results showed that breastfeeding peer support had an effect in reducing early complementary feeding. OR values showed 11,000 (95% CI: 1,998-60,572) this meant that breastfeeding peer support had a risk of 11 times lowering breastfeeding mothers' behavior in giving early complementary feeding. Conclusions: breastfeeding peer support affects the reduction of early complementary feeding in breastfeeding mothers.